Comparative evaluation of fracture healing potential of differentiated and undifferentiated guinea pig and canine bone marrow-derived mesenchymal stem cells in a guinea pig model. (June 2022) - Peer, Bilal Ahmad; Bhat, Abas Rashid; Shabir, Uffaq; Bharti, Mukesh Kumar; Bhat, Irfan Ahmad; Pandey, Sriti; Sharun, Khan; Kumar, Rohit; Mathesh, Karikalan; Saikumar, Gutulla; Chandra, Vikash; Amarpal; et al.
Abstract: Background and aim: This work was conducted to compare the therapeutic potential of undifferentiated and osteogenic differentiated canine (xenogeneic) and guinea pig (allogeneic) BMSCs in fracture healing using guinea pig as a model. Materials and methods: A well-characterized homogenous population of third passage mesenchymal stem cells of bone marrow origin was used in all the experiments. MSCs from both the species, i.e., canine and guinea pigs, were differentiated and characterized. Expression of MHC I and II along with co-stimulatory molecules was assessed based on relative mRNA expression. The osteogenic differentiated and undifferentiated MSCs from both species were used for evaluating fracture healing in the guinea pig model. The healing potential was assessed based on radiographic, histopathology, and clinical observations. Results: BMSCs from both species expressed MSC surface antigens and successfully differentiated to osteogenic, chondrogenic, and adipogenic lineages. The mRNA expression of class I and II MHC molecules in all the three lineages showed no significant (p > 0.05) differences after differentiating to adipogenic, chondrogenic, and osteogenic lineages. Radiographic and clinical examination revealed that MSCs therapy significantly improved bone fracture healing with a non-significant (p > 0.05) difference between differentiated and undifferentiated BMSCs. In addition, allogeneic MSCs therapy performed better than xenogeneic therapy. Conclusion: MSCs remained hypo immunogenic after differentiation and have comparable fracture healing potential though allogeneic MSCs have better therapeutic potential than xenogenic MSCs. Highlights: BMSCs implantation improves bone healing in the treatment group irrespective of the cell source. Transplantation of allogeneic MSCs may provide better bone healing than xenogeneic MSCs. The expression of MHC class II did not change significantly after differentiation. Canine BMSCs express a low level of MHC class I surface antigen, which gets further downregulated after differentiation.